Determinants of the firm value of listed banks in Pakistan: A panel data approach - Jagirani, Tahir Saeed; Chee, Lim Chee; Kosim, Zunarni Binti (Asian Economic and Financial Review, 2023)
The aim of this study is to examine the determinants of firm value for listed banks in Pakistan. This study is based on secondary data extracted from the annual reports of listed banks in Pakistan with quarterly data comprising 512 sample observations from 2015 to 2021. Panel data estimation techniques were employed for the analysis. The findings of the study revealed that all determinants influence firm value except liquid assets to total assets (LATA). The stock price of listed banks in Pakistan is continuously falling, which causes the stock's value to change from being overpriced to being undervalued. Nonperforming loans (NPLs) and the cost-to-income ratio (CIR) reduce firm value, while increases in the net interest margin (NIM) and capital adequacy ratio (CAR) enhance firm value. Further, NPLs and the CIR have a negative relationship with firm value. However, CAR, LATA, and NIM have positive associations with the firm value. The study concluded that the average capital adequacy ratio of listed banks in Pakistan is 10.5%, which is higher than the minimum requirement set by the regulator. This indicates that CAR helps to increase firm value in listed banks in Pakistan. The study will be useful to policymakers, regulators, and the banking sector in evaluating the major determinants that affect firm value.